The Use of Velocity Information in Movement Reproduction - Chieffi, Sergio; Messina, Antonietta; Villano, Ines; Valenzano, Anna A.; Nigro, Ersilia; La Marra, Marco; Cibelli, Giuseppe; Monda, Vincenzo; Salerno, Monica; Tafuri, Domenico; Carotenuto, Marco; Cipolloni, Luigi; et al. (Frontiers in Psychology, 2017)
Background: Previous studies suggest that movement velocity influence space perception. Aim and Objectives: We examined whether healthy participants spontaneously used velocity information when they were asked to reproduce a previously carried out movement. Two experiment were carried out. Materials and Methods: In experiment 1, blindfolded participants actively performed an arm movement (criterion movement, CM) at a natural velocity, or quickly, or slowly. After a brief delay, participants were asked to reproduce (reproduction movement, RM) CM-amplitude. No velocity constraints were imposed in making RM. In experiment 2, CM was performed quickly or slowly. After a brief delay, the participants were asked to reproduce not only CM-amplitude but also CM-velocity. Results: Experiment 1. In Natural condition, RM-velocity did not differ from CM-velocity and the participants accurately reproduced CM-amplitude. Conversely, in Fast and Slow conditions, RM-velocities differed from CM-velocities and in Slow condition RM-amplitude was greater than CM-amplitude. Experiment 2. Both RM-amplitude and -velocity did not differ from CM-amplitude and -velocity. Conclusion: The present study suggests that movement velocity influenced space perception and this influence was more evident for slow than fast movements. Furthermore, although velocity information was crucial in reproducing accurately CM-amplitude, it was not spontaneously used.